0429 Respiratory Safety of Lemborexant in Adult and Elderly Subjects with Mild Obstructive Sleep Apnea. (12th April 2019) - Cheng, Jocelyn; Moline, Margaret; Filippov, Gleb; Murphy, Patricia; Bsharat, Mohammad; Hall, Nancy
Abstract: Introduction: Lemborexant (LEM) is a dual-orexin-receptor antagonist under development for the treatment of insomnia and irregular sleep-wake rhythm disorder. As concerns regarding current sleep-promoting drugs include central respiratory depression (benzodiazepines) and limited safety evidence in vulnerable individuals such as the elderly (nonbenzodiazepine receptor agonists) and individuals with obstructive sleep apnea (OSA), it is important that LEM demonstrate safety in these groups. The primary objective of this study was to determine whether multiple LEM doses increased apnea-hypopnea index (AHI) in adult and elderly subjects with mild OSA versus placebo (PBO) using polysomnography (PSG). Secondary objectives included whether AHI increased and peripheral oxygen saturation (SpO2) decreased after single and multiple doses, and if SpO2 decreased below defined thresholds. Methods: This was a multicenter, multiple-dose, randomized, double-blind, PBO-controlled, 2-period crossover study in adult (age <65y) and elderly (age ≥65y) subjects with mild OSA (5≤AHI<15). Subjects were randomized to two 8-night treatment periods (separated by a washout ≥14d) with either LEM 10mg (LEM10) or PBO. In-lab PSG was performed at screening and on the first and last nights of both treatment periods. Results: Thirty-nine subjects were randomized. The majority were White and female (61.5% each). Mean age was 57.2y; 66.7% were <65y and 33.3% were ≥65y. Mean baseline SpO2 (94.8%) and AHI (9.0) were comparable across treatment sequences. There was no significant difference in AHI (least squares mean) after single or multiple doses of LEM10 versus PBO (single: LEM10, 10.29; PBO, 10.22, P=0.979; multiple: LEM10, 9.93; PBO, 10.00, P=0.948). Similarly, there were no significant differences for LEM10 versus PBO in SpO2 after multiple or single doses (single: LEM10, 94.62%; PBO, 94.54%, P=0.699; multiple: LEM10, 94.65%; PBO, 94.39%, P=0.169), nor were there statistically significant differences from PBO for SpO2 below the thresholds of <90%, <85%, <80%, and for the presence of ≥1 incident of SpO2 <90% ≥30 seconds. Conclusion: LEM demonstrates respiratory safety with multiple and single dosing in adult and elderly subjects with mild OSA, as objectively measured by AHI and SpO2. Support (If Any): Eisai Inc., Purdue Pharma L.P